2015
DOI: 10.11113/jt.v77.6690
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Nematode Resistance to Anthelmintic Drugs in Two Goat Farms in Terengganu

Abstract: Gastrointestinal nematodes considered to be among the factors that could affect the goats’ productivity. The objective of this study was to evaluate the current status of nematode resistance to anthelminthic drugs in two farms (Veterinary Research Academy Jenang, Marang and Hulu Seladang Setiu Farms). The goats were randomly divided into five treatments which include control (A), albendazole oral administration (B), levamisole oral administration (C), ivermectin subcutaneous injection (D) and ivermectin pour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The current study was the only test that had verified resistance to all four of the anthelmintics tested. This problem of resistance to multiple anthelmintics is becoming more evident globally (Byaruhanga et al, 2013;Nabukenya et al, 2014;Abubakar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study was the only test that had verified resistance to all four of the anthelmintics tested. This problem of resistance to multiple anthelmintics is becoming more evident globally (Byaruhanga et al, 2013;Nabukenya et al, 2014;Abubakar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found GIN resistance to every class (Terrill et. al., 2001;Zajac and Gipson, 2000;Abubakar et. al., 2015).…”
Section: Introductionmentioning
confidence: 99%